2015
DOI: 10.5539/ass.v11n14p337
|View full text |Cite
|
Sign up to set email alerts
|

Current Problems of Interstate Cooperation of Russian Federation for the Protection of Children in Case of Disputes between Parents Living in Different States

Abstract: In 2011 and 2013 the Russian Federation has become a State party to two important international treaties on the protection of human rights of children -Convention on the Civil Aspects of International Child Abduction of 1980 and Hague Child Protection Convention of 1996. Considering the social significance of these conventions, there is a practical need in the elaboration of the procedure of their application by the state organs as well as the organisation of knowledge-raising campaign aimed at disseminating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In 2011 and 2013 the Russian Federation has become a State party to two important international treaties on the protection of human rights of childrenConvention on the Civil Aspects of International Child Abduction of 1980 (Abashidze et al, 2015a) and the Convention on Jurisdiction, Applicable Law, Recognition, Enforcement and Co-operation in respect of Parental Responsibility and Measures for the Protection of Children's Rights of October 19, 1996-Hague Child Protection Convention of 1996 (Abashidze et al, 2015b). This is especially important to outline, as in the 90-th of the XX century in Russian Federation, there have been significant changes in the social, economic and cultural spheres.…”
Section: Introductionmentioning
confidence: 99%
“…In 2011 and 2013 the Russian Federation has become a State party to two important international treaties on the protection of human rights of childrenConvention on the Civil Aspects of International Child Abduction of 1980 (Abashidze et al, 2015a) and the Convention on Jurisdiction, Applicable Law, Recognition, Enforcement and Co-operation in respect of Parental Responsibility and Measures for the Protection of Children's Rights of October 19, 1996-Hague Child Protection Convention of 1996 (Abashidze et al, 2015b). This is especially important to outline, as in the 90-th of the XX century in Russian Federation, there have been significant changes in the social, economic and cultural spheres.…”
Section: Introductionmentioning
confidence: 99%
“…SADC Tribunal concluded that it had jurisdiction to hear the case because the dispute concerns "human rights, democracy and the rule of law" (Abashidze, et al, 2015), which are the fundamental principles for the SADC Member States.…”
Section: The Fatal Case "Michael Campbell Against Zimbabwe"mentioning
confidence: 99%